2019
DOI: 10.30595/jssh.v3i1.3843
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Fear of Negative Evaluation in Foreign Language Anxiety: Photovoice of Undergraduates in Speaking Class

Abstract: Foreign Language Anxiety (FLA) is a common situation happens in EFL classroom. This phenomenon usually causes the students' anxiety while they are learning English. The previous study proved that language learners performed significantly better on oral foreign language if they were in less anxious situations. Students' unwillingness for participating speaking activities in the classroom caused by their assumption of being judged negatively and lack of mastering the speaking skill. The objective of this researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
5
0
3
Order By: Relevance
“…As mentioned by Ok and Ustaci (2013), being corrected by class instructors could be one of the sources of anxiety as teachers or instructors are seen as a knowledgeable person who possesses the right skill in the teaching of foreign language. With 3.3 is the overall score for mean, this shows that respondents agree that low self-confidence has prompted learners to experience fear of negative evaluation as they believe that they will be judged by their performance in the language class (Wardhani, 2019).…”
Section: Fear Of Negative Evaluationmentioning
confidence: 97%
“…As mentioned by Ok and Ustaci (2013), being corrected by class instructors could be one of the sources of anxiety as teachers or instructors are seen as a knowledgeable person who possesses the right skill in the teaching of foreign language. With 3.3 is the overall score for mean, this shows that respondents agree that low self-confidence has prompted learners to experience fear of negative evaluation as they believe that they will be judged by their performance in the language class (Wardhani, 2019).…”
Section: Fear Of Negative Evaluationmentioning
confidence: 97%
“…The findings indicate that students experienced fear of negative evaluation in communication and interaction in English language classes. Previous studies found fear of negative evaluation as one of the main sources of language anxiety (Mukminin et al 2015;Wardhani, 2019;Sadighi & Dastpak, 2017). Though, test anxiety got the lowest mean score, the participants still suffer from test anxiety.…”
Section: What Is the Level Of Foreign Language Speaking Anxiety Among...mentioning
confidence: 88%
“…Fear of negative evaluation (FNE) is defined as "apprehension about others' evaluation, avoidance of evaluative situations, and the expectation that others would evaluate oneself negatively" p:128. Fear of negative evaluation is a wider area because it is not restricted to test-taking environment, but it may happen in any situation such as during interviewing for a job or interacting in foreign language class (Horwitz et al, 1986;Toyama & Yamazaki, 2018;Wardhani, 2019). Learners who are concerned with FNE tend to be unsuccessful to start conversation or feel lack of ability to make suitable social impression (Liu, 2018;Karatas et al, 2016).…”
Section: Fear Of Negative Evaluationmentioning
confidence: 99%
“…The theoretical indications are further supported by a fundamental pilot study based on the productive language usage of foreign language students (n=108) and the corresponding reflective and prospective analysis. Next research by Alif (2019) Students' unwillingness for participating in speaking activities in the classroom caused by their assumption of being judged negatively and lack of mastering the speaking skill. The researchers collected and processed the data using Photovoice.…”
Section: Past Studies On Fear Of Learning Foreign Languagesmentioning
confidence: 99%